2016
DOI: 10.31018/jans.v8i3.930
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical response to higher temperature stress in hot pepper (Capsicum annuum L.)

Abstract: The present study was conducted to evaluate the physiological and biochemical changes in some thermotolerant and thermosensitive chilli (Capsicum annuum L.) genotypes. Fourteen chilli genotypes (SL 461, PP 404, DL 161, MS 341, VR 521, PB 405, PS 403, SD 463, FL 201, AC 102, S 343, SL 462 and SL 464 along with sensitive check [Royal Wonder of bell pepper] were evaluated for heat tolerance. The observations on morpho-physiological and biochemical parameters were recorded at 45, 65, 85 and 105 days after transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…In cucumber (Cucumis sativus L.) or watermelon (Citrulus lanatus L.), temepratures above 35 • C caused a reduction in flowers and sugar content [113]. In hot pepper, temperatures of 38 • C caused a reduction in flowers and fruits number [114], while temperatures of 40 • C altered the size of the bulbs and increased the sulfur content in onion [115,116]. In tomato plants, tempeartures above 25 • C reduced the number of fruits and flowers, the content of lycopene and carotene and caused fruit discoloration [117].…”
Section: Implications Of Heat For Nutritional and Functional Quality ...mentioning
confidence: 99%
“…In cucumber (Cucumis sativus L.) or watermelon (Citrulus lanatus L.), temepratures above 35 • C caused a reduction in flowers and sugar content [113]. In hot pepper, temperatures of 38 • C caused a reduction in flowers and fruits number [114], while temperatures of 40 • C altered the size of the bulbs and increased the sulfur content in onion [115,116]. In tomato plants, tempeartures above 25 • C reduced the number of fruits and flowers, the content of lycopene and carotene and caused fruit discoloration [117].…”
Section: Implications Of Heat For Nutritional and Functional Quality ...mentioning
confidence: 99%
“…In hot pepper, the temperature more than 30 °C not only significantly reduces the pollen viability, and fruit set 9 , 10 and yield 11 , 12 , but induces the abscission of floral buds, flowers and immature fruits 11 , 13 . Various hot pepper accessions with diverse genetic backgrounds significantly differ in response to heat stress 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Proline played a role in mitigating the deleterious effects (Nawaz et al, 2010). Ghai et al (2016) in their studies indicated that heat stress greatly reduced the chlorophyll contents values in plants. Transpiration rate increased in response to heat stress (Cui et al, 2006) and showed recovery upon exogenous proline application.…”
Section: Discussionmentioning
confidence: 98%